2023
DOI: 10.1002/hsr2.1733
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effect of polyurethane dressing containing silver particles on the rate of diabetic foot ulcer infection in hospitalized patients: A randomized control study

Saeideh Hosseinpoor,
Fatemeh Kalroozi,
Maryam Nezamzadeh
et al.

Abstract: Background and AimsOne of the new types of dressings is the polyurethane dressing containing silver particles. This study was designed to evaluate the effect of polyurethane dressing containing silver particles on the rate of diabetic foot ulcer infection in hospitalized patients in a military hospital.MethodsThis was a randomized clinical trial study on 48 patients with diabetic foot ulcers who were referred to the wound clinic of Shahid Dr. Chamran Hospital in 2022. The qualified samples were divided into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…It is extensively used in the treatment of burn wounds in burn. 14 In this investigation, we found that FD and MVD significantly contributed to the wound healing rate and FD is more effective than MVD. Diabetes causes chronic low-grade inflammation and a protracted inflammatory response following injury, which can negatively impact wound closure.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…It is extensively used in the treatment of burn wounds in burn. 14 In this investigation, we found that FD and MVD significantly contributed to the wound healing rate and FD is more effective than MVD. Diabetes causes chronic low-grade inflammation and a protracted inflammatory response following injury, which can negatively impact wound closure.…”
Section: Discussionmentioning
confidence: 59%
“…The application of a polyurethane dressing containing silver particles is more effective in reducing the rate of diabetic ulcer infection than the simple sterile dressing. 14 A high-absorption polyurethane FD modified by polyethylene glycol and triethoxysilane promotes diabetic wound healing through micro-negative-pressure generation facilitated by its high absorption capacity and deformation. 15 Micropower vacuum dressing (MVD) is a new wound dressing with negative pressure materials to strongly absorb blood or liquid seeps by forming the “pump effect”.…”
Section: Introductionmentioning
confidence: 99%
“… 26 , 27 , 28 In a recent randomized controlled study, the polyurethane dressing containing silver particles was shown to be more effective in reducing the infection rate in patients with diabetic foot ulcers (DFUs) compared to the simple sterile dressing. 29 For the treatment of other chronic wounds such as venous leg ulcer, pemphigus vulgaris and incisional wound, silver‐containing dressings can also accelerate the wound healing and reduce wound infection compared to conventional non‐silver dressing. 12 , 13 , 30 These findings are consistent with the conclusion of our study.…”
Section: Discussionmentioning
confidence: 99%